Active learning, its concept, importance, and some of its strategies (Journal of the College of Basic Education, 2023)
Active learning derives its philosophy from contemporary global and local variables. It is a response to these variables by reconsidering the roles of the teacher and the learner, and making the learner the focus of the educational process. Therefore, the current research emphasized the importance of active learning and its ability to change the image of the teacher as the only source of knowledge, and the need to reconsider the roles of both the teacher and the learner in the educational situation. The current research aims to identify the concept of active learning and its importance in the educational process. The research may consist of three chapters. The first chapter was titled (General Concepts of Active Learning), while the second chapter was titled (The role of both the teacher and the learner in active learning). The third chapter, in which the researcher talked about selected strategies in active learning, represented by the project-based learning strategy, the round table strategy, and the learning strategy together. The researcher hopes that he has been successful in his research in talking about active learning and its importance in the educational process, and directing the attention of those in charge of the educational process to the need to build and develop curricula in stages.